A Case Study Approach to Human Resources Management. - Sadri, Sorab (Himalaya Pub. House, 2009)
As the saying goes, theory without practice is puerile and practice without theory is futile. The professor in this book has taken care to Apoint out, there must be a symbiotic relationship between theory and practice and in B-Schools. This realisation is very important. The student enters the portal of the academia as raw material and leaves it as a final product only to be absorbed for gainful employment by the ultimate customer in the civil society. This understanding of the conversion of theory to practice is often made possible through a proper use of the case study method. In the course.